Efficient solid phase extraction of α-tocopherol and β-sitosterol from sunflower oil waste by improving the mesoporosity of the zeolitic adsorbent - Karaoglu, Oznur; Alpdogan, Guzin; Zor, Sule Dinc; Bildirir, Hakan; Ertas, Erdal (ELSEVIER SCI LTD, 2020)
The recovery of alpha-tocopherol and beta-sitosterol from the deodorizer distillate of sunflower oil using solid phase extraction is reported. Performance of the silicon-rich and inexpensive zeolite, ZSM-5, and its modified versions were compared as adsorbents. Modifications of the zeolite frame were performed under both acidic and basic conditions to desilicate and dealuminate the parent ZSM-5. Base treatment resulted in hierarchical porosity and increased mesoporosity in the structure, which made the desilicated material as the best adsorbent of the study. Optimization of the solid phase extraction conditions was also studied and high recoveries of alpha-tocopherol and beta-sitosterol, up to 99.20% and 97.32%, respectively, were achieved. The preparation and characterisation of the reported sorbents, as high-performance adsorbents, were not only proved to be economically promising, due to recycling of nutritious products, but also improves the ecological credentials of the process through reduction in waste.
Keywords: Solid phase extraction (SPE); Mesoporous zeolite; ZSM-5; Sterol; Tocopherol; Sunflower oil waste; Response surface methodology (RSM); BY-PRODUCTS; HIGH-PURITY; DEALUMINATION; DESILICATION; SEPARATION; TRENDS; Chemistry; Food Science & Technology; Nutrition & Dietetics